2020
DOI: 10.1051/e3sconf/202020402008
|View full text |Cite
|
Sign up to set email alerts
|

Research on Day-ahead Dispatch of Electricity-heat Integrated Energy System Based on Improved PSO Algorithm

Abstract: With the increasingly serious environmental pollution, it is of great significance to construct a comprehensive day-ahead dispatch model of the integrated energy system. For the regional electricity-heat integrated energy system, firstly analyze the operating characteristics and dispatch costs of all units in the system, and then establish the day-ahead economic dispatch model of the system. Furthermore, an improved PSO algorithm is designed based on the idea of adaptive weight and genetic algorithm, and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Genetic algorithms and particle swarm algorithms are two algorithms that are often used in energy planning projects [10][11][12]. However, research has demonstrated that using a pure genetic algorithm or a particle swarm approach to determine the best solution for energy planning is problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic algorithms and particle swarm algorithms are two algorithms that are often used in energy planning projects [10][11][12]. However, research has demonstrated that using a pure genetic algorithm or a particle swarm approach to determine the best solution for energy planning is problematic.…”
Section: Introductionmentioning
confidence: 99%